A Double-Hurdle Model of Healthcare Expenditures across Income Quintiles and Family Size: New Insights from a household Survey - Ahmad Reshad Osmani; Albert Okunade (Journal of Risk and Financial Management, 2021)
The decision-making processes and outcomes of male and female household heads differ due to gender-based differences in preferences. In this paper we assess the impact of this heterogeneity on household healthcare consumption in Thailand. Past studies modeling healthcare expenditures using household survey data used a gender dummy in regression models to control for household gender headship at the household level. Due to the endogeneity and self-selection bias in the past modelling approach, we separately modeled health expenditures for male and female household head decision makers. Using household dataset from an earlier work, this study finds, using the double-hurdle model with dependent errors, that out-of-pocket health care spending tends to behave like a necessity across the income quintiles, household sizes, and differently for the separately modeled household gender heads. Moreover, male and female headed households responded differently to a major economic shock when adjusting household healthcare spending.
Keywords: C50; D13; I12; I15; 330; household-head gender; household health expenditure; double hurdle model; elasticity; Health Capital